Simulation Approach in Evaluating the Electromagnetic fields from the new lines of Extra High Voltage (EHV) circuits near residential area in Malaysia - Rahman N.A.; Mahadi W.N.L.; Said I.; Hussain H. (EuroJournals, Inc., 2023)
This paper presents a study which is carried out on the new lines of Extra High Voltage (EHV) transmission lines specifically on the quadruple circuits of 132kV and double circuits of 500kV tower designs. There were assumptions made by various clusters of communities in Malaysia highlighting the effects on EMF radiation emitted from towers to the surrounding area. These effects were somehow claimed to be standing within the dangerous limits and disturbed many residents. The radiation studies involving EHV transmission lines in Malaysia are rarely undertaken since a lot of work had been focused entirely on the low levels of high voltage lines. Authorities and the regulators such as Tenaga National Berhad (TNB) was pushed to draw the guidelines as well as producing firm decisions generally on the issues of EMF management and its protection strategy. An initial case had been identified which involve various sites which is visible and passing through the public residential areas. The lines were located within the Klang Valley areas which are having the highest density populated area in Malaysia. The study comprises work from the evaluation of the electric and magnetic fields of both design types and also simulation studies using Fields 2.0 software. This includes comparison of both results in actual site measurements and simulations with actual setting parameters as its input data. The outcome of this paper will be the results analysis on field characterizations during normal load operations and predictions on high load conditions progressing to justify the exact safety distances for publics. EuroJournals Publishing, Inc. 2010 Simulation Approach in Evaluating the Electromagnetic Fields from the New Lines of Extra High Voltage (EHV) Circuits Near Residential Area in Malaysia.